Grounding the Applicability of Eloquent Theoretical Waqf for Rural Waste Management: A Case Study of the Gresik Industry Region - Hudaifah, Ahmad; Prasetya, Fandi Angga; Cholilie, Irvan Adhin; Tutuko, Bambang (Universitas Islam Internasional Indonesia, 2022)
Like many other cities, the industrial region of Gresik encounters problematic issues inherent in the burgeoning quantities of waste in landfill sites despite frequent policy implementations and other efforts from the local government. This study aims to examine and interlink between the possibility of the waqf concept and the growing number of waste issues in the Gresik industrial region. By harnessing ethnographical principles such as employing direct and consistent observations and reviewing numerous relevant literature surveys and archival documents, the study attempts to propose an executable design and model that will serve as a framework for stakeholders to address the weaknesses of current less favourable waste treatment programs. A comprehensive and rigorous consideration concludes that the viability of waqf can be a workable prospect and nucleus for an alternative solution and a complementary voluntary enhancement of effective regional policies and programs. An actionable and contributable waqf aspiration can start from the reformulation and rejuvenation of a rural waste bank which is designed to manage an effective balance between profitable and eco-friendly objectives. Professionalism and competence are significant factors in successfully enhancing the functionality of such an institution. Apart from the micro perspective, the bigger picture of a nexus of waqf and waste, including the current intermittent commitment from top policy makers transferred into timely execution, futuristic applicable technology, charitable giving and donation, and sensible collaborative cooperation, constitutes the conceivable determinants for the accomplishment of an efficacious program.